Malaysia as a culinary tourism destination : international tourists' perspective / M. Shahrim Ab. Karim, Bee-Lia Chua and Hamdin Salleh - Ab. Karim, M. Shahrim; Chua, Bee-Lia; Salleh, Hamdin (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA, Puncak Alam Campus, 2009)
This study was conducted to determine Malaysia's current food image and food attribute satisfaction from international tourists' points of view and subsequently assess their overall satisfaction with the eating experience and behavioral intention. The results indicated that Malaysia possesses clear images of 'core food value', 'Malaysian food specialty', and 'Malaysian food uniqueness' but is rather unclear on the images of 'food and dining atmosphere' and 'features of Malaysian food'. Tourists' satisfaction with 'quality and value of food' and 'accessibility convenience' were relatively higher than 'dining atmosphere' and 'culinary tourism products'. Regression analyses revealed that food images and food attributes' satisfaction significantly predicted tourists' overall satisfaction, and the overall satisfaction revealed a significant relationship with tourists' behavioral intentions. Implications for managers who are involved in food tourism are posited.